The mitral to aortic/pulmonary velocity-time integral ratio is a simple, feasible and accurate discriminator for echocardiographic evaluation of severe isolated mitral regurgitation. (3rd October 2022) - Ramkumar, S; Nerlekar, N; Maggiore, P; Teng, J; Cimenkaya, C; Be, K; Baumann, A; Nicholls, S; Moir, S
Abstract: Background: Echocardiographic quantification of mitral regurgitation (MR) remains challenging, requiring dedicated image acquisition, and is limited by potential error from geometric assumptions of annular dimensions. Volume is a product of area and flow and assuming proportional mitral/aortic areas, an increased mitral-inflow volume compared to LV/RV-outflow semi-quantitatively represents greater MR regurgitant volume. Therefore, we investigated the feasibility and diagnostic performance of the mitral-aortic velocity-time integral (VTI) ratio in isolated MR. We also investigated the use of the mitral-pulmonary VTI ratio as an alternative in clinical situations where the LV outflow tract (LVOT) VTI could not be used. Methods: We reviewed 166 consecutive patients (54 (33% severe MR by multi-parameter integrated expert opinion)). Pulsed-Doppler VTI at the mitral leaflet tips and the left ventricular outflow and continuous-wave Doppler of the right ventricular outflow tract were measured individually and independently by blinded readers (expert and trainee status) to derive the ratio. Receiver operator characteristic area under the curve (AUC) comparison was calculated and compared with effective regurgitant orifice area (EROA >40 mm), regurgitant volume (RVol >6 0mL), vena contracta (VC >0.7 cm), E-velocity >1.2 cm, systolic flow reversal (SFR), left atrial and ventricular dilatation. Results: Increasing ratio was associated with severe MR (AUC 0.94) with optimal threshold defined at 1.3. This provided significant discrimination for severe MR (AUC 0.81) compared to EROA (0.68), VC (0.52), LV dilatation (0.69), LA dilatation (0.70), SFR (0.73), E-velocity (0.68) all p<0.05, with sensitivity 82% and specificity 94%. The mitral-pulmonary VTI ratio demonstrated similar discrimination (AUC 0.92) with optimal threshold defined at 1.14. Excellent inter-observer reproducibility (intra-class correlation 0.97) was seen between trainee and expert readers. There was no difference in AUC comparison by MR mechanism or patient rhythm. Conclusions: The mitral-aortic or mitral-pulmonary VTI ratio is a simple, geometric-free parameter feasibly reproducible from routine echocardiographic datasets and is an excellent discriminative tool for severe MR. Readers should consider integration of this parameter in routine reporting. Funding Acknowledgement: Type of funding sources: None.